Efficacy and safety of current treatment options for peripheral retinal haemangioblastomas: a systematic review. Issue 1 (8th April 2021) - Hajjaj, Anass; van Overdam, Koen A.; Gishti, Olta; Ramdas, Wishal D.; Kiliç, Emine
Abstract: Importance: Approximately twenty per cent of Von Hippel–Lindau patients with retinal haemangioblastomas (RH) suffer from visual impairment. Various treatment options are available for peripheral RH. However, management of peripheral RH is complex due to multifocality and bilaterality. Objective: To summarize published evidence on efficacy and safety of different interventions for peripheral RH and to provide treatment recommendations for specialists. Evidence review: Comprehensive searches were performed using Medline, Embase, Web of Science and Google Scholar database on 4 March 2020. English publications that described outcomes related to efficacy or complications in at least two patients with peripheral RH were included. Efficacy and safety were estimated by complete tumour eradication rate, pretherapeutic and treatment‐related complication rate. Odds ratios (OR) with 95% confidence intervals (CI) were calculated to calculate the risk estimate of complications between treatment options. Findings: Twenty‐seven articles were included in this review describing nine different treatment options for peripheral RH: laser photocoagulation ( n  = 230), cryotherapy ( n  = 50), plaque radiotherapy ( n  = 27), vitreoretinal surgery ( n  = 88), photodynamic therapy (PDT; n  = 14), transpupillary thermotherapy (TTT; n  = 10), external beam radiotherapy ( n  = 3), systemic treatment ( n  = 7) and intravitreal anti‐VEGF ( n  = 2). Complete tumour eradication was achieved in 86.7% (95% CI: 83.5–89.9%) of all eyes. For the different treatments, this was after laser photocoagulation 89.9% (86.1–93.7%), cryotherapy 70.2% (57.0–83.4%), plaque radiotherapy 96.3% (89.1–100.0%), vitreoretinal surgery (100.0%), PDT 64.3% (38.3–90.3%) and TTT 80.0% (53.8–100.0%). No complete tumour eradication was achieved after systemic therapy, external beam radiotherapy or intravitreal anti‐VEGF. Photodynamic therapy and vitreoretinal surgery showed the highest complication rate after treatment compared to the other treatments (OR 10.5 [95% CI: 2.9–38.4]) and (OR 5.9 [95% CI: 3.4–9.9]), respectively. Cases that had pretherapeutic complications showed a higher treatment‐related complication rate (OR 14.8 [95% CI: 7.3–30.0]) than cases without complications before treatment. Conclusions and Relevance: These findings suggest that laser photocoagulation is the safest and most effective treatment method for peripheral RH up to 1.5 mm in diameter. Vitreoretinal surgery has the highest success rate for complete tumour eradication and may be the most suitable treatment option in the presence of pretherapeutic complications and for larger tumours.